A comparative life cycle assessment of graphene and activated carbon in a supercapacitor application. (1st January 2020) - Cossutta, Matteo; Vretenar, Viliam; Centeno, Teresa A.; Kotrusz, Peter; McKechnie, Jon; Pickering, Stephen J.
Abstract: Graphene shows substantial promise in improving the technical performance of a range of applications. For its development and before its potential mass adoption, it is critical to understand the associated cradle-to-grave life cycle environmental impacts. Previous studies on graphene environmental performance do not include end of life and the potential environmental credits generated by graphene reuse. This study undertakes a cradle-to-grave approach to evaluating graphene applications, considering a case study of supercapacitors manufactured with graphene and activated carbon active materials. The analysis includes active materials commercial-size production, supercapacitors production, supercapacitors use phase in an automotive application, and their end of life in which both devices are recycled. With current material performance and energy mixes, the graphene-based supercapacitor would increase impacts in all environmental categories analysed, ranging from 27% higher human toxicity to 213% greater ozone depletion and showing a 48% increase in GHG emissions. This unfavourable result arises due to the tested graphene material exhibiting inferior specific capacitance to the activated carbon comparator, as well as a more energy-intensive production process. Prospective analysis considers hypothetical performance where both active materials reach their theoretical specific capacitance, and the decarbonisation of electricity generation. The environmental impacts of both the activated carbon and graphene supercapacitors are reduced in these prospective scenarios, with the graphene based supercapacitor becoming the least impacting solution due to its lower active material requirements. The graphene-based device shows 36% lower GHG emission and overall shows lower impacts ranging from 14% less mineral, fossil and renewable resource depletion to 43% less photochemical ozone formation. These results support graphene as a valid candidate material for substituting activated carbon in supercapacitors provided graphene technical performance is improved, production optimised, and recycling developed. Graphical abstract: Image 1 Highlights: Activated carbon supercapacitors show the lowest environmental impact. Recycling of graphene is key to reduce its environmental impacts. Prospective LCA indicates graphene supercapacitors as the least impacting.